The feasibility and cost of a large multicentre audit of process and outcome of prostatectomy. Issue 4 (December 1995) - Emberton, M; Neal, D E; Black, N; Harrison, M; Fordham, M; McBrien, M P; Williams, R E; McPherson, K; Develin, H B
Abstract : Objective–To determine the feasibility of performing multicentre process and outcome audits of common interventions taking prostatic procedures as an example. Design–Prospective, cohort study. Setting–All National Health Service and independent hospitals in Northern, Wessex, Mersey, and South West Thames health regions. Patients–5361 men undergoing prostatectomy identified by 103 of the 107 urologists and general surgeons performing prostatectomy in the study regions. Main measures– Rates of participation by surgeons and patients; completeness of clinical data provided by surgeons; patient response rate and completeness of patient derived data; and cost. Results–Most surgeons (103, 96%) agreed to participate. Overall, the proportion of eligible patients invited to take part was high (89%), although this was only measured in South West Thames, where dedicated data collectors were employed. Few men (80, 1.5%) declined to participate. Of those surviving for three months after surgery, 82.4% (4226) completed and returned the postal questionnaire. The response rate was higher in South West Thames (86.7%) than in the other regions (80.6%-80.8%). The audit was well received: 91% of patients found the questionnaire easy to complete and only 2.3% of them disapproved. Completeness of data was high with both the hospital and patient questionnaires. Missing data occurred in less than 5% of responses to most questions. The attributable cost was 34.50 pounds per patient identified or 44 pounds for patients in whom either the treatment outcome or vital status was known three months after their prostatectomy. Conclusions–This multicentre audit of process and outcome of prostatectomy proved feasible in terms of surgeon participation, patient identification, and the quantity and quality of data collection. Whether the cost was warranted will depend on how surgeons use the audit data to modify their practice.